Business Process Model And Notation Untuk Memodelkan Proses Pengingat Pinjaman Pada Koperasi - David Diamanta; Alva Hendi Muhammad (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2025)
Savings and loan cooperatives are strategic microfinance institutions facing challenges in managing loan reminder processes. XYZ Savings and Loan Cooperative operates manual reminder processes without standard documentation, creating risks of human error and operational inefficiency. This study aims to design Business Process Model and Notation (BPMN) to model and standardize loan reminder processes at XYZ Savings and Loan Cooperative. The research employed a qualitative approach with descriptive analytical methods. Data collection was conducted through direct observation for one month, interviews with the Secretary Department Cooperative Employee, and internal document studies. Business process analysis was performed to understand existing workflows, then modeled into BPMN elements using Bizagi Modeler software. Model validation was conducted through structured questionnaires with 20 validation aspects. BPMN model was successfully designed with two main scenarios namely Friday reminder process as the main process and Monday reminder process with follow-up mechanisms. The model involves three main actors (Cooperative Members, Cooperative Employees, and Cooperative Head) with clear swimlane divisions. The process starts from attendance checking, WhatsApp messaging, phone calls, to coordination for direct visit scheduling. Validation shows perfect conformity of 100% from 20 evaluated aspects. The BPMN model successfully transformed manual processes without documentation into structured and standardized visualization. The study concludes that BPMN implementation can effectively standardize previously manual and undocumented loan reminder processes, producing standard documentation that can be implemented for procedure standardization and new employee literacy, thereby improving operational effectiveness and reducing human error risks in cooperative loan reminder processes.